Geochemistry of ore-forming fluids, Deh-Salm uneconomic porphyry Mo system, SW Nehbandan, Iran: a fluid inclusion investigation. Issue 3 (4th May 2019) - Hezarkhani, Ardeshir; Ghannadpour, Seyyed Saeed
ABSTRACT: Based on the fluid inclusion and rock sample geochemistry in Deh-Salm hydrothermal system, it is shown that uneconomic molybdenite mineralization occurred in both stockwork- and limited skarn-type alterations. Homogenization temperatures and salinities based on microthermometry data are presented for fluid inclusions from hydrothermal quartz associated with pyrite, galena, sphalerite and rare molybdenite mineralization. The data indicate that ore mineral precipitation occurred within a temperature range of 250° to > 490°C from moderate to high-salinity (9 to > 42 wt% NaCl equivalent) aqueous fluid. Two stages of hydrothermal activity characterized by high-salinity fluids (> 30 wt% NaCl equivalent) are identified; 1) relatively high-temperatures (350° to > 490°C); 2) lower temperatures (170° to 250°C). The high-salinity, high-temperature stage is interpreted to be the evidence for resurgent boiling. Dilution of these fluids by convicting meteoric water resulted in low to moderate salinity fluids, which dominated the inclusion population in quartz hosted crystals. The high-salinity, low-temperature fluid inclusions identify the residual fluids derived from boiling which happened as a result of a change in the pressure regime from dominantly lithostatic to hydrostatic conditions. Condensation and infiltration of ground waters caused major chemical variations, increasing the hydrostatic pressure, and the acid-washed processes on the system. The intense acid-washed and the intrusive rock depth is suggested to be the main reasons caused an uneconomic metal deposition in Deh-Salm system.